Customer Retention Model – A Case Study of a Branded Passenger Car - Wong, Lai Soon; de Run, Ernest Cyril; Ngerng, Miang Hong (-, 2012)
Current automobile players are facing steep competition but no empirical study on antecedents of customers’ repurchase intention of a branded passenger car has been done. A conceptual framework that integrates three previous frameworks has been developed to understand current car owner repurchase intention. A multi-stage sampling scheme, cluster followed by random sampling was used to select 450 respondents for a questionnaire survey; out of which 360 completed responses were used in analysis. The response was analyzed through Structural Equation Modeling (SEM). The findings indicate that trust and customer satisfaction are crucial driving factors in customers’ repurchase intention. Customer’s perceptions about service, product quality and price fairness are the foundations in building customer satisfaction. The estimated SEM portrait the multi-relationships among the six construct. This model presents is much more informative then those reported before and the findings can be of significant contribution to a car manufacturer endeavor in customer’s retention.